2009
DOI: 10.1126/science.1179713
|View full text |Cite
|
Sign up to set email alerts
|

Selective Phenol Hydrogenation to Cyclohexanone Over a Dual Supported Pd–Lewis Acid Catalyst

Abstract: Cyclohexanone is an industrially important intermediate in the synthesis of materials such as nylon, but preparing it efficiently through direct hydrogenation of phenol is hindered by over-reduction to cyclohexanol. Here we report that a previously unappreciated combination of two common commercial catalysts-nanoparticulate palladium (supported on carbon, alumina, or NaY zeolite) and a Lewis acid such as AlCl3-synergistically promotes this reaction. Conversion exceeding 99.9% was achieved with >99.9% selectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
464
3
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 606 publications
(500 citation statements)
references
References 28 publications
13
464
3
5
Order By: Relevance
“…On the basis of these results, it can be concluded that the phenol hydrogenation proceeds through the pathways illustrated in Scheme 1: phenol is sequentially hydrogenated through cyclohexanone to cyclohexanol (paths i and iii) and directly to cyclohexanol (path ii). In contrast to the present results, almost 100% selectivity to cyclohexanone was obtained with supported Pd catalysts in both the gas-phase [1][2][3][4][5][6][7][8][9][10][11][12] and liquid-phase [13][14][15][16]25] hydrogenation reactions. The direct formation of cyclohexanol from phenol (path ii) is unlikely to occur with these Pd catalysts.…”
Section: Reaction Pathways Of Phenol Hydrogenationcontrasting
confidence: 99%
See 3 more Smart Citations
“…On the basis of these results, it can be concluded that the phenol hydrogenation proceeds through the pathways illustrated in Scheme 1: phenol is sequentially hydrogenated through cyclohexanone to cyclohexanol (paths i and iii) and directly to cyclohexanol (path ii). In contrast to the present results, almost 100% selectivity to cyclohexanone was obtained with supported Pd catalysts in both the gas-phase [1][2][3][4][5][6][7][8][9][10][11][12] and liquid-phase [13][14][15][16]25] hydrogenation reactions. The direct formation of cyclohexanol from phenol (path ii) is unlikely to occur with these Pd catalysts.…”
Section: Reaction Pathways Of Phenol Hydrogenationcontrasting
confidence: 99%
“…This may result from stronger acidity of Al 2 O 3 support compared with active carbon. Liu et al point out the significance of Lewis acidity of support materials in determining the high selectivity to the formation of cyclohexanone, which is prevented from being hydrogenated to cyclohexanol by interactions between the acid sites and the cyclohexanone [25]. Table 3 The effects of CO 2 pressurization were greatly different between Rh/C and Rh/Al 2 O 3 catalysts.…”
Section: Comparison Of Rh/c and Rh/al 2 Omentioning
confidence: 99%
See 2 more Smart Citations
“…[36][37][38][39] The underlying origin of the metal-support interaction and the promotional role of the active oxide supports in enhancing the catalytic activity and selectivity have thus been extensively studied. [40][41][42][43][44][45][46][47] Relatively, little is known about direct interfacial interaction between metal NPs and support oxide NPs in a confined geometry. It would thus be interesting to study noble metal and active metal oxide with a welldefined nanostructure, which will render an important clue to elucidate the proximal metal-oxide interaction in nanometer scale [48][49][50] and will also give a chance to develop a hybrid catalytic system on the basis of metal and oxide.…”
Section: Introductionmentioning
confidence: 99%